Teachers’ Perspectives on Engaged Teaching: Study from an American Curriculum School in Dubai - Albasha, Wafa (2019)
An engaged learning environment requires educators to motivate and encourage students to achieve their educational goals. Therefore, a student-centred approach is preferred to the teacher-centred one. The study aimed towards identifying negative and positive implications of engaged learning under the American curriculum system. Special emphasis was placed on schools in UAE and specifically in Dubai, where there has been an increasing number of American curriculum schools. The theories that have been applied in the study include engagement theory, behavioural theory and the Vygotsky’s Social learning theories of engaged learning. In addition, the study utilises the various concepts in learning including, constructivist, active, passive, cooperative, and engaged learning. The study applied qualitative research approach in the exploring the teacher’s perspective regarding engaged learning in the American Curriculum in Dubai where observations and interviews were done. The key finding of the study is that assessment during engaged learning represented meaningful performance elements and if they represent equitable learning standards applicable to all students. The current study has identified cooperative learning as vital in any form of engaged learning based on the analysis of the interviews and observations conducted in the study. Cooperative learning encourages teamwork and eliminates unnecessary competition in the classroom which can have negative effect on the learning process as well as promotes accountability in the schools.